2023
DOI: 10.1111/1750-3841.16848
|View full text |Cite
|
Sign up to set email alerts
|

Effects of lycopene on the growth performance, meat quality, and antioxidant capacity of broiler chickens challenged with aflatoxin B1

Huimin Ma,
Qi Chen,
Haiming Yang
et al.

Abstract: The present study aimed to investigate the effects of dietary lycopene (LYC) supplementation on the growth performance, meat quality, and antioxidant capacity of breast muscle in aflatoxin B1 (AFB1)‐challenged broilers. A total of 192 1‐day‐old healthy Arbor Acres broilers were randomly assigned to 3 treatments, each with 8 replicates (8 broilers per replicate). The broilers of the three treatments were fed a basal diet (control), a basal diet supplemented with 100 µg/kg AFB1 (CA), and a basal diet supplemente… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 49 publications
0
2
0
Order By: Relevance
“…Muscle color depends on myosin oxidation and light reflection from free water [46]. Ma et al [47] found that dietary lycopene supplementation decreased muscle lightness L* and shear force in broiler chickens. In this study, the breast muscle L* at 24 h after slaughter in the groups treated with 20 mg/kg and 30 mg/kg dietary lycopene was reduced, which may be because, under the action of oxygen, lycopene converted the myoglobin in muscle into oxymyoglobin and continued to be oxidized to ferrimyoglobin, which made the muscle color relatively darker [48].…”
Section: Effects Of Dietary Lycopene On the Meat Quality In Broiler C...mentioning
confidence: 99%
“…Muscle color depends on myosin oxidation and light reflection from free water [46]. Ma et al [47] found that dietary lycopene supplementation decreased muscle lightness L* and shear force in broiler chickens. In this study, the breast muscle L* at 24 h after slaughter in the groups treated with 20 mg/kg and 30 mg/kg dietary lycopene was reduced, which may be because, under the action of oxygen, lycopene converted the myoglobin in muscle into oxymyoglobin and continued to be oxidized to ferrimyoglobin, which made the muscle color relatively darker [48].…”
Section: Effects Of Dietary Lycopene On the Meat Quality In Broiler C...mentioning
confidence: 99%
“…Lycopene has also been shown to be antitoxic to AFB 1 in other species. Studies have demonstrated that lycopene reduced liver and intestinal damage induced by AFB 1 in broilers and improved their growth and development performance. Sahar et al discovered that adding 100 mg/kg of lycopene to the feed for 10 days provided protective benefits to the liver and kidney of Pekin duckling exposed to AFB 1 . This protection was attributed to the elevation of antioxidant protein levels, total antioxidant capacity (TAC), and phase II enzyme activity …”
Section: Multiple Phytochemicals Against Afb1 Toxicitymentioning
confidence: 99%